Dithiocarbamate derivatives inhibit α‐glucosidase through an apparent allosteric site on the enzyme. (19th June 2021) - Ghani, Usman; Ashraf, Sajda; Ul‐Haq, Zaheer; Mujamammi, Ahmed H.; Özkay, Yusuf; Demirci, Fatih; Kaplancikli, Zafer Asim
Abstract: Dithiocarbamate derivatives possess diverse biological activities. This work further expands their activity profile by identifying seven benzylamine‐containing dithiocarbamate derivatives with piperazine and piperidine substitutions at the main moiety, and five piperazine‐containing dithiocarbamates with various substitutions at the piperazine moiety as new inhibitors of α‐glucosidase. Compounds bearing the benzylamine moiety exhibited more potent inhibition of the enzyme than the piperazine derivatives. Majority of the compounds non‐competitively inhibited α‐glucosidase that led to the identification of a new allosteric site on the enzyme with the help of molecular dynamics and docking studies. These studies suggest that the compounds regulate inhibition of the enzyme by binding to an allosteric site that is located in the vicinity of the active site. This is the first report on the allosteric inhibition of α‐glucosidase by dithiocarbamate derivatives that provides insights into the mechanism of inhibition of the enzyme at molecular level. Moreover, it also explores new avenues for drug development of α‐glucosidase inhibitors as antidiabetic drugs. Abstract : Dithiocarbamate derivatives containing piperazine and piperidine moieties inhibit α‐glucosidase enzyme by binding to an apparent allosteric site.